STUDY ON CONTACT DAMAGE OF WIND POWER GEARS BASED ON CONFIGURATIONAL FORCE THEORY - YE Nan; ZHANG YanHui; WANG Rong; LIU Ran; ZHANG ChuanFen; OUYANG Heng; DUAN ShuYong (Jixie qiangdu)
The gear box of wind turbine is in the complex environment such as random wind load for a long time， and the gear contact fatigue becomes a key factor limiting the stability and reliability of wind turbine equipment. The research on the gear contact damage evolution mechanism was faced with difficulties such as complex stress states， damage anisotropy and failure modeling. Material configurational force theory can describe the effect of defect configurational change on the free energy of materials and can be used to predict the damage and failure behavior of materials. A wind turbine gear contact damage model was constructed based on this theory. The gear contact interface stress field simulation analysis was carried out for the key bearing area of gear contact， and the gear contact damage evolution process under contact load was simulated. The research results have shown that the configurational force theory damage model can effectively simulate the contact damage phenomenon of gear and explain the pitting and spalling of gear surfaces. It has theoretical significance to predict contact fatigue life of gear accurately.